ANALYSIS OF THE EFFECT OF BUSINESS CAPITAL AND WORKING HOURS ON MSME INCOME IN SURABAYA CITY (case study of a coffee shop in Sukolilo sub-district) - Andjarwati, Tri; Endah Budiarti; Muhamad Yasin (Jurnal Ekonomi, 2022)
The coffee shop itself is just a place that provides and sells coffee management products, ready-to-serve coffee, besides that the coffee shop business offers food and soft drinks. Coffee shops are included in small individual-owned businesses that can make it easier for Indonesian people to get jobs and improve the economy. The coffee shop itself does not require to have special skills in blending coffee using more modern technology. This study aims to determine the effect of working capital and working hours on the income of a coffee shop business in Sukolilo District, Surabaya City. The type of research used is quantitative with multiple linear regression analysis, t-test and f-test and correlation analysis of determination using SPSS 26. This study took samples from the number of coffee shop entrepreneurs in Sukolilo District. The number of samples used as many as 40 respondents. The variables used in this study are working capital variables, working hours which are independent variables, and income as the dependent variable. Based on multiple linear regression analysis, the following results were obtained Y = 1.310 + 0.603X1 +0.992X2 + e. This means that the variables of working capital and working hours have a positive effect on the income of coffee shops in Sukolilo District. The results of the t-test indicate that the venture capital variable partially has a significant positive effect on the income of the coffee shop business in Sukolilo District. It can be proven that the variable X_(1 ) has a t_count of 8,557 which is greater than t_table of 1,68830. The variable working hours partially has a positive effect on the income of coffee shops in Sukolilo District. It can be proved that the variable X_2 has t_(count ) of 3.768 which is lower than t_table of 1.68830. The results of the f test show that the capital variable and can simultaneously have a significant effect on the income of the coffee shop business in Sukolilo District. This can be seen from the sig value of 0.000. The value of F_(count )(33.099) is greater than F_(table ) (3.29).